PI3K/mTOR Inhibitors in the Treatment of Luminal Breast Cancer. Why, When and to Whom? - Schettini, Francesco (Breast Care (Basel), 2017)
Estrogen receptor (ER) signaling represents the main driver of tumor growth and survival in luminal breast cancer (BC). Despite the efficacy of endocrine agents, many patients with luminal BC do not respond to endocrine therapy and many others develop endocrine resistance over time, due to the activation of escape pathways such as the PI3K/AKT/mTOR signaling. Several clinical trials have demonstrated the efficacy of mTOR and PI3K inhibitors in overcoming endocrine resistance in hormone receptor-positive human epidermal growth factor receptor 2 (HER2)-negative metastatic BC (MBC) patients. Nevertheless, to date, everolimus is the only agent targeting the PI3K/mTOR pathway that has been approved for clinical use. Recently, the introduction of CDK 4/6 inhibitors into clinical practice has significantly changed the therapeutic scenarios in luminal MBC. In the absence of direct comparisons among the new treatment combinations and predictive biomarkers of response, the choice of optimal therapeutic algorithms is very challenging. Future trials should focus on identifying more effective and safe combination therapies and defining the best treatment sequences in luminal BC.